An Ultracompact Multimode Waveguide Crossing Based on Subwavelength Asymmetric Y-Junction - Weijie Chang; Luluzi Lu; Xinshu Ren; Longhui Lu; Mengfan Cheng; Deming Liu; Minming Zhang (IEEE Photonics Journal)
We propose and experimentally demonstrate a novel ultracompact multimode waveguide crossing. The compact asymmetric subwavelength Y-junction is introduced to convert the high-order modes into fundamental ones, enabling one to implement three or more modes simultaneously in the subsequent processing. Our proposed device occupied only a compact footprint of 34 × 34 μm2. The measured results indicate our fabricated device exhibited a high performance with the insertion loss less than 0.9 dB, crosstalk lower than –24 dB from 1.52 to 1.60 μm for all the three modes. Moreover, our scheme could be easily expended to implement more modes and will show great potential in dense and large-scale on-chip photonic integration.